Ultra Low Power ECG Processing System for IoT Devices - Tekeste Habte, Temesghen; Saleh, Hani; Mohammad, Baker; Ismail, Mohammed (Analog Circuits and Signal Processing,, 2019)
This book describes an ECG processing architecture that guides biomedical SoC developers, from theory to implementation and testing. The authors provide complete coverage of the digital circuit implementation of an ultra-low power biomedical SoC, comprised of a detailed description of an ECG processor implemented and fabricated on chip. Coverage also includes the challenges and tradeoffs of designing ECG processors. Describes digital circuit architecture for implementing ECG processing algorithms on chip; Includes coverage of signal processing techniques for ECG processing; Features ultra-low power circuit design techniques; Enables design of ECG processing architectures and their respective on-chip implementation.